Spatiality of Social Stress Experienced by Refugee Women in Initial Reception Centers - Mehran Nassim; Abi Jumaa Jinan; Lazaridou Felicia; Foroutan Naika; Heinz Andreas; Kluge Ulrike (Journal of International Migration and Integration, 2021)
This study takes an interdisciplinary approach to understanding the multi-dimensionality of social stress within the spatiality of initial refugee reception centers in Berlin. By focusing particularly on the experiences of women who fled from Syria and Afghanistan, it situates this humanitarian issue within an analytical framework of gender-sensitive and culturally sensitive research and policymaking. Through qualitative interviews with 11 refugee women, the connection between the spatiality of initial reception centers and social stress is explored. This is done by thematically coding the data collected in the context of nine different initial reception centers across various districts in the city of Berlin. The study shows that in terms of the intercultural needs and practices of these women, social stress is triggered by a lack of essential privacy within the spatiality of these structures. However, privacy is not limited to a physical enclosure—it is about having control/freedom over different aspects of everyday life. This article highlights intercultural gaps in gender-sensitive and protection considerations during humanitarian responses.
Keywords: 300; Spatiality; Social stress; Refugee women; Reception centers; Privacy; Resettlement